2019
DOI: 10.1111/jdv.15614
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy use in UK primary care: a survey of GPs with a special interest in dermatology

Abstract: Background Melanoma accounts for 90% of skin cancer mortality and typically presents in primary care, where it can be challenging to distinguish from benign lesions. Dermoscopy is a tool for skin visualization that is routinely used for melanoma diagnosis in secondary care. However, the role of dermoscopy in primary care remains unclear. Objectives To determine views on, and use of, dermoscopy by dermatology‐interested general practitioners (GPs). Methods An online questionnaire was emailed to the UK Primary C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 32 publications
2
30
0
1
Order By: Relevance
“… 66 One study suggested that 1 day of live training in dermoscopy was sufficient to build the confidence of GPs with special interest in melanoma diagnosis. 67 We found two RCTs that demonstrated sustained improvement in GPs’ diagnostic accuracy, both of which proposed live training in dermoscopy over 1 day or 10 hours. 9 10 Because the duration of training in dermoscopy is a limiting factor for most GPs, it is important to keep in mind that training in clinical melanoma diagnosis has also been shown to improve the GPs’ performances while requiring less training time (in this review, a mean duration of 2.5 hours was observed for clinical diagnostic training programmes).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“… 66 One study suggested that 1 day of live training in dermoscopy was sufficient to build the confidence of GPs with special interest in melanoma diagnosis. 67 We found two RCTs that demonstrated sustained improvement in GPs’ diagnostic accuracy, both of which proposed live training in dermoscopy over 1 day or 10 hours. 9 10 Because the duration of training in dermoscopy is a limiting factor for most GPs, it is important to keep in mind that training in clinical melanoma diagnosis has also been shown to improve the GPs’ performances while requiring less training time (in this review, a mean duration of 2.5 hours was observed for clinical diagnostic training programmes).…”
Section: Discussionmentioning
confidence: 89%
“… 71 In the UK, a survey among GPs with special interest in dermatology stated that self-assessment learning was the most popular for refresher sessions. 67 Nevertheless, they also showed that 36% of GPs who use dermoscopy in their clinical practice reported to have never updated their training skills. We found that the most appreciated form of self-assessment updates was the unlimited access to an e-learning course.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical picture of most dermatological diseases is often indistinguishable, so that even dermatologists themselves use further diagnostic tools such as dermatoscopy to certify the diagnosis of a disease and to solve differential diagnostic issues. 22 Short-term education to these diagnostic techniques will be very useful. 23 Since the volume of dermatological diseases is so high, more and more targeted training is needed for general practitioners on these diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Professional training is necessary for dermatologists, and dermatologists without training perform no better with a dermoscope than with naked eye examinations. [2] Although regular training courses have been offered, either face-to-face or online, only a small number of dermatologists have received systematic and long-term training. Improving the dermatologist's ability to use a dermoscope is one of the necessary conditions for ensuring the accuracy of disease diagnosis.…”
Section: Future Trend Of Dermoscopy In Chinamentioning
confidence: 99%
“…Sub-surface structures such as the epidermis, dermal papilla, and color can be better observed in vivo , by eliminating surface reflection at the skin air interface. [2] Dermoscopy can improve the diagnostic sensitivity for various types of skin disorders without reducing the specificity. [3] In addition, dermoscopy can help dermatologists to better define the tumor margin, measure post-treatment effects and classify diseases.…”
Section: Introductionmentioning
confidence: 99%